2015
DOI: 10.3390/molecules200916770
|View full text |Cite
|
Sign up to set email alerts
|

Acetylated Rhamnogalacturonans from Immature Fruits of Abelmoschus esculentus Inhibit the Adhesion of Helicobacter pylori to Human Gastric Cells by Interaction with Outer Membrane Proteins

Abstract: Polysaccharide containing extracts from immature fruits of okra (Abelmoschus esculentus) are known to exhibit antiadhesive effects against bacterial adhesion of Helicobacter pylori (H. pylori) to stomach tissue. The present study investigates structural and functional features of polymers responsible for this inhibition of bacterial attachment to host cells. Ammonium sulfate precipitation of an aqueous extract yielded two fractions at 60% and 90% saturation with significant antiadhesive effects against H. pylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 25 publications
(53 reference statements)
5
22
0
Order By: Relevance
“…The study also found that okra aqueous extract could inhibit the adhesive binding of BabA, SabA, and HpA to its specific ligands, and several compounds from okra aqueous extract could non-specifically bind to different H. pylori strains, as well as to BabA/SabA-deficient mutants. Another study analyzed the structures of polysaccharides from immature okra which possessed anti-adhesive activity, and confirmed the presence of acetylated rhamnogalacturonan-I polymers, decorated with short galactose side chains (Thöle, Brandt, Ahmed, & Hensel, 2015). It was also suggested that esterification of the extracts was necessary for the anti-adhesive activity.…”
Section: Anti-adhesive Activitymentioning
confidence: 93%
“…The study also found that okra aqueous extract could inhibit the adhesive binding of BabA, SabA, and HpA to its specific ligands, and several compounds from okra aqueous extract could non-specifically bind to different H. pylori strains, as well as to BabA/SabA-deficient mutants. Another study analyzed the structures of polysaccharides from immature okra which possessed anti-adhesive activity, and confirmed the presence of acetylated rhamnogalacturonan-I polymers, decorated with short galactose side chains (Thöle, Brandt, Ahmed, & Hensel, 2015). It was also suggested that esterification of the extracts was necessary for the anti-adhesive activity.…”
Section: Anti-adhesive Activitymentioning
confidence: 93%
“…The recent work of Xu et al [81] reported molecular characteristics and rheological properties of water-extractable polysaccharides derived from okra ( Abelmoschus esculentus L.): the proportions of galacturonic acid and monosaccharides in the refined polysaccharides were 62.47% and 13.47%, respectively. Some reports have mentioned that okra polysaccharides are associated to several bioactivities linked to diabetes management, i.e., hypoglycemic activity, and are indicated as novel immunomodulators [37,82,83], in addition to others [84,85,86,87,88]. Fan et al [37] reported that okra polysaccharide can lower body weight and glucose levels, improve glucose tolerance, and decrease total serum cholesterol levels in high-fat diet-fed C57BL/6 mice: okra polysaccharide regulated the gene expression of liver X receptors (LXRs) and peroxisome proliferator-activated receptors (PPARs) and their target genes in the liver and in the adipose tissue of the mice; the same authors [37] suggested that okra polysaccharide may have therapeutic effects on metabolic diseases via the inhibition of LXR and PPAR signaling.…”
Section: An Updated Overview Of Potential Beneficial Effects Assocmentioning
confidence: 99%
“…Okra pods can be consumed as a new health vegetable of high nutritional value, which are rich in polyphenol, vitamins, dietary fiber, calcium, and other bioactive substances (Camciuc, Deplagne, Vilarem, & Gaset, 1998;Sankar et al, 2008) with beneficial-health functions, for example anti-oxidation, anti-caries, anti-obesity, anti-diabetes, anti-inflammation, and anti-cardiovascular disease, etc. (Adelakun, Oyelade, Ade-Omowaye, Adeyemi, & Van de Venter, 2009;Thole, Brandt, Ahmed, & Hensel, 2015). As it is easy to grow, okra has recently been planted extensively in most parts of vast areas in China (Huang & Zhang, 2015).…”
Section: Introductionmentioning
confidence: 99%